LIFE PLANS AS A FUNCTIONAL AREA FOR PREVENTION OF SOCIAL MALADJUSTMENT OF YOUTH - Paweł Kozłowski (Probacja)
The article approximates the topic of the concepts of life plans of adolescents. Their diagnostic, cognitive importance in the formation of social maladjustment in the situation of collapse of the life plan was indicated. Also their motivational value in the preventive process of restructuring, rebuilding the life plans. The results of the research on the life plans of adolescents were also presented and analyses were made in terms of their diversity due to gender, age, school class, average grades and behavioral evaluation. The motivational, qualitative, functional, subjective potential of life plans of adolescents in the process of motivating constructive change, which is an important dynamic in terms of individualized prophylactic treatment paving the way for resolution in the pre-trial proceedings. The potential of application of life plans of young people in the formation of prevention of social maladjustment of young people was also shown, especially at the selective and indicative level in terms of individual activity in the perspective of certain provisions of national and international law concerning minors.